Immunosuppressive metabolites in tumoral immune evasion: redundancies, clinical efforts, and pathways forward - David Munn; Maria Rain Jennings; John Blazeck (Journal for ImmunoTherapy of Cancer)
Tumors accumulate metabolites that deactivate infiltrating immune cells and polarize them toward anti-inflammatory phenotypes. We provide a comprehensive review of the complex networks orchestrated by several of the most potent immunosuppressive metabolites, highlighting the impact of adenosine, kynurenines, prostaglandin E2, and norepinephrine and epinephrine, while discussing completed and ongoing clinical efforts to curtail their impact. Retrospective analyses of clinical data have elucidated that their activity is negatively associated with prognosis in diverse cancer indications, though there is a current paucity of approved therapies that disrupt their synthesis or downstream signaling axes. We hypothesize that prior lukewarm results may be attributed to redundancies in each metabolites’ synthesis or signaling pathway and highlight routes for how therapeutic development and patient stratification might proceed in the future.